2020
DOI: 10.1093/qjmed/hcaa193
|View full text |Cite
|
Sign up to set email alerts
|

Feeding vessel sign: a radiological sign of septic pulmonary embolism

Abstract: Feeding vessel sign is very sensitive radiological finding of septic pulmonary embolism. In the appropriate clinical context, if the CT scan of a patient with suspected sepsis shows this radiological sign, empirical antibiotics (including gram positive organisms) should be started at the earliest after sending all cultures to decrease mortality and morbidity. Here we are presenting a case of 14-years-old boy with left ankle septic arthritis and septic pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This aspect is key to distinguishing SPE from other types of pulmonary embolism. The feeding vessel sign [5,6] has been reported in the literature as a characteristic of SPE. In our patient, we performed emergency CT imaging within 24 hours of acute onset, and feeding vessel signs were found.…”
Section: Discussionmentioning
confidence: 96%
“…This aspect is key to distinguishing SPE from other types of pulmonary embolism. The feeding vessel sign [5,6] has been reported in the literature as a characteristic of SPE. In our patient, we performed emergency CT imaging within 24 hours of acute onset, and feeding vessel signs were found.…”
Section: Discussionmentioning
confidence: 96%
“…Typical CT findings may include nodules and/or cavities located mostly in the area close to peripheral vessel terminations (a sign of feeding vessel; Fig. 2), infiltrates, wedge-shaped lesions adjacent to the pleura, pleural effusion, focal consolidation, and abscess [6][7][8]. The most critical factor for disease prognosis is to consider SPE and start broad-spectrum antibiotic therapy early [3][4][5].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The mortality rate in SPE is between 10 and 20% and is mainly caused by septic shock and multiorgan failure. Early diagnosis and prompt antibiotic therapy determine the prognosis of the disease [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The feeding vessel sign represents a vessel leading directly to the nodule [ 84 ]. Some studies have found that a “halo sign” and “feeding vessel sign” are more frequent in SPE secondary to Gram-negative bacteria, whereas the cavitation and bronchograms are more common in Gram-positive bacterial embolisms [ 29 ].…”
Section: Septic Embolismmentioning
confidence: 99%
“…Some studies have found that a “halo sign” and “feeding vessel sign” are more frequent in SPE secondary to Gram-negative bacteria, whereas the cavitation and bronchograms are more common in Gram-positive bacterial embolisms [ 29 ]. The feeding vessel sign, which indicates the hematogenous nature of the nodules, is not specific for septic pulmonary embolism, as this image can be found in other diseases, such as bland pulmonary embolism and hematogenous metastasis [ 29 ], arteriovenous malformation, pulmonary vasculitis and pulmonary infarction [ 84 ]. Multi-detector CT is superior to the classical CT when we want to point up the feeding vessel sign [ 18 ].…”
Section: Septic Embolismmentioning
confidence: 99%